Automated Reasoning 8th International Joint Conference, IJCAR 2016, Coimbra, Portugal, June 27 - July 2, 2016, Proceedings - Olivetti, Nicola; Tiwari, Ashish (Lecture Notes in Artificial Intelligence,, 2016)
This book constitutes the refereed proceedings of the 8th International Joint Conference on Automated Reasoning, IJCAR 2016, held in Coimbra, Portugal, in June/July 2016. IJCAR 2014 was a merger of three leading events in automated reasoning, namely CADE (International Conference on Automated Deduction), FroCoS (International Symposium on Frontiers of Combining Systems) and TABLEAUX (International Conference on Automated Reasoning with Analytic Tableaux and Related Methods). The 26 revised full research papers and 9 system descriptions presented together with 4 invited talks were carefully reviewed and selected from 79 submissions. The papers have been organized in topical sections on satisfiability of Boolean formulas, satisfiability modulo theory, rewriting, arithmetic reasoning and mechanizing mathematics, first-order logic and proof theory, first-order theorem proving, higher-order theorem proving, modal and temporal logics, non-classical logics, and verification.